2020
DOI: 10.1016/j.jdeveco.2019.102429
|View full text |Cite
|
Sign up to set email alerts
|

Rural transformation, inequality, and the origins of microfinance

Abstract: , as well as participants at various conferences and seminars for insightful feedback and suggestions. Matthias Barelkowski, Sophie Bartosch, Julian Richter, André Wiesner and Iris Wohnsiedler provided invaluable research assistance. All errors remain our own.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 61 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…Moneylenders dare provide cash fast, available at any time, blend in with the community, simple administration process, serve small loans in short terms and offer daily repayments [6], [40]. Suesse and Wolf [41] decided to enter an MFI depending on existing informal loans, and Sangeetha and Chitra [42] that interest rates are one of the impacts of competition between MFIs and money lenders on market outcomes. As a result, poor people involved in moneylender loans are limited in participating and benefiting from the development opportunities [5], [35].…”
Section: B Analysis Of Efas (External Factors Analysis Summary) or Ef...mentioning
confidence: 99%
“…Moneylenders dare provide cash fast, available at any time, blend in with the community, simple administration process, serve small loans in short terms and offer daily repayments [6], [40]. Suesse and Wolf [41] decided to enter an MFI depending on existing informal loans, and Sangeetha and Chitra [42] that interest rates are one of the impacts of competition between MFIs and money lenders on market outcomes. As a result, poor people involved in moneylender loans are limited in participating and benefiting from the development opportunities [5], [35].…”
Section: B Analysis Of Efas (External Factors Analysis Summary) or Ef...mentioning
confidence: 99%
“…Geographic location, baseline inequality levels, and baseline population size affected the relationship between income inequality and population change. Suesse and Wolf [ 15 ] found that structural restructuring causes credit cooperatives to arise from dropping agricultural staple prices and declining bank lending. Land inequality and low asset sizes hindered regional cooperative growth, while ethnic heterogeneity had mixed consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Modern microfinance dates back to the innovative lending in rural areas by the Grameen Bank of Bangladesh in the 1970s but the concept has emerged as a solution for the challenges of rural credit markets across space and time (Suesse & Wolf, 2020). Yet, much of the microfinance growth has been due to its expansion in urban markets as a response to rapid urbanization and increased attention to urban poverty (Armend ariz & Morduch, 2010).…”
Section: Introductionmentioning
confidence: 99%